HERDING BEHAVIOUR AROUND FED FUND RATE ANNOUNCEMENTS IN SOUTHEAST ASIA - Arisanti, Ike (Universitas Muhammadiyah Malang)
This study aims to detect herding behavior in the Southeast Asian capital market after the announcement of the fed fund rate in 2018. The population used in this study are all companies listed on the Indonesia, Malaysia, Thailand, Vietnam, Philippines stock exchanges. The sample collection technique in this study used purposive sampling. The method used to detect herding behavior using CSAD was developed by Chang, Cheng, and Khorana (2000). The results of the study found a herding behavior. . Empirical test results from the regression showed the coefficient Î³2 is negative and meets the level of confidence at the level of 95%. The ability of the regression results to meet the expected level of confidence, then empirically this can conclude the existence of herding behavior. This means supporting the hypothesis in Hi, thus in aggregate it appears that during the observation period herding behavior occurred after the Fed Fund Rate 2018 was announcedÂ Keywords : Fund Fed Rates, Herding, Southeast Asia